Pedagogia das competências: reflexões críticas sobre sua influência no contexto contemporâneo - Betiate, Francieli Aparecida (2024)
This dissertation contains the results of a study within the History of Education research line, which focuses on the Pedagogy of Competencies in the contemporary context. This pedagogical orientation emerged in Brazil with a focus on the formation of specific competencies to meet the demands of globalization, especially about the job market, based on philosophical research anchored in neoliberal ideology. The guiding question of the research is: Does the Pedagogy of Competencies contribute to the de-characterization of public schools, and if so, how does this happen? The hypothesis is that the Pedagogy of Competencies contributes to the de- characterization of public schools by prioritizing the training of specific skills aligned with the demands of the job market and, consequently, sidelining the transmission of systematized knowledge. The general objective was to analyze the pedagogy Pedagogy of competences Competences in the contemporary school context, especially in Brazil, and to. To do this, we sought to understand its foundations mainly from Philippe Perrenoud's (1999, 2000) defense of this pedagogy. The critique and counterpoints to the Pedagogy of Competences were based on the Historical-Critical Pedagogy in terms of its conception of school and human formation, based on Duarte (2006, 2008, 2010), Ramos (2001, 2002, 2003), Kuenzer (2002, 2005), Paiva (1989, 1999) and Saviani (2007, 2008), as well as the curricula of the Association of Municipalities of Western Paraná (AMOP) and the city of Cascavel - PR, whose original orientation differs from the Law of Guidelines and Bases of National Education and the National Common Curriculum Base, which, in turn, support the Pedagogy of Competencies. As far as methodology is concerned, bibliographic research was carried out based on the theoretical framework of the dialectical materialist method. As a result, it was found that the Pedagogy of Competencies effectively contributes to the de-characterization of public schools.